The effect of rainfall on the spread of malaria in Indonesia - Faradiba, Faradiba (International Journal Of Community Medicine And Public Health, 2021)
Background: Indonesia's territory consists of a large number of islands stretching from Sabang to Merauke. This condition causes different levels of development between regions. The eastern region of Indonesia is relatively slow when compared to the western region. This has resulted in the eastern region being in pristine condition and filled with forests. The climate in eastern Indonesia tends to be humid, resulting in high development of the female Anopheles mosquito, the cause of malaria. Methods: The use of the instrumental variable method is necessary, because the model has endogeneity problems. The data used in this study comes from the results of the 2018 Podes data and climate data. Results: The results of this study indicate that rainfall affects the number of malaria incidents and has a positive impact on mortality due to malaria, with coefficients of 0.0000779 and 0.0000142, respectively. Conclusions: Education is needed for the community to minimize malaria, which often occurs, generally in the Papua region. Through health promotion, it is hoped that the community will be able to live cleanly and healthily, as well as change their behavior in life, considering that the area is vulnerable to malaria.